Proceedings of the 20th International ACM SIGACCESS Conference on Computers and Accessibility 2018
DOI: 10.1145/3234695.3240997
|View full text |Cite
|
Sign up to set email alerts
|

The Present and Future of Museum Accessibility for People with Visual Impairments

Abstract: People with visual impairments (PVI) have shown interest in visiting museums and enjoying visual art. Based on this knowledge, some museums provide tactile reproductions of artworks, specialized tours for PVI, or enable them to schedule accessible visits. However, the ability of PVI to visit museums is still dependent on the assistance they get from their family and friends or from the museum personnel. In this paper, we surveyed 19 PVI to understand their opinions and expectations about visiting museums indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 10 publications
(16 reference statements)
0
19
0
2
Order By: Relevance
“…BLV people are interested in visiting museums and wish to know about artwork [68][69][70]. However, a number of accessibility issues exist when visiting and navigating inside a museum [71]. While audio guide services are in operation for some exhibition sites [72][73][74][75], it can still be difficult for BLV people to understand the spatial arrangement of objects within each painting.…”
Section: Accessart For Artwork Accessibilitymentioning
confidence: 99%
“…BLV people are interested in visiting museums and wish to know about artwork [68][69][70]. However, a number of accessibility issues exist when visiting and navigating inside a museum [71]. While audio guide services are in operation for some exhibition sites [72][73][74][75], it can still be difficult for BLV people to understand the spatial arrangement of objects within each painting.…”
Section: Accessart For Artwork Accessibilitymentioning
confidence: 99%
“…Afterwards, one of our internal researchers manually classified each keyword into one of the three categories if applicable. As for the rest, nouns and meaningless words like 'is' or 'not' were removed and its parts of speech was checked using WordNet from Python NLTK package 4 . For all 8 paintings, the object keywords were the most frequent (23.2%), followed by hue, location, status, other, shape, size, brightness, texture(18.0%, 14.3%, 10.4%, 10.0%, 8.3%, 4.8%, 4.2%, 3.4%, respectively.…”
Section: Content Analysis Of Object Annotationsmentioning
confidence: 99%
“…Still, we recommend providing the overall description in addition to object-level descriptions of artwork for the ones who wish to get more information including other people's interpretations. As a result, although verifying an ability of people to understand the artwork is difficult, we suggested the method to judge the ability of PVI to independently interpret or even criticize the paintings as an extension of prior works [4,33].…”
Section: Understanding Artwork From Object-level Descriptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…They stated that the requests of visually disabled individuals are in contrast with one of the most critical duties of museums, which is the displaying of artwork and while protecting it at the same time. Asakawa et al (2018) conducted a survey on visually impaired people to explain their experiences and motivations to visit and the accessibility problems they faced. Their study revealed that the participants are overly eager to visit the museums to satisfy their desire to learn and gain value the experience.…”
Section: Literature Reviewmentioning
confidence: 99%